SCIENCE EDUCATION IN OUTDOOR LEARNING ENVIRONMENTS FROM THE PERSPECTIVE OF PRESCHOOL TEACHERS: DEFINITIONS, OPPORTUNITIES, OBSTACLES, AND POSSIBLE SOLUTIONS - Nagihan TANIK ÖNAL,; Ebru EZBERCİ ÇEVİK , (MOJES: Malaysian Online Journal of Educational Sciences, 2022)
The present study aims to reveal the opinions of pre-school teachers concerning science education in outdoor learning environments in terms of the definition of the subject matter, opportunities, obstacles, and possible solutions. 105 pre-school teachers participated in this study. In the study, a questionnaire consisting of open-ended questions prepared by the researchers was used as a data collection tool. The collected data were analyzed with two-step content analysis. As a result, teachers define outdoor learning as learning everywhere outside of school, the environments where they think that science activities can be carried out is mostly park-garden-forest, nine of the teachers do not teach science from outside of school, 13 of them do partially, 83 teachers stated that they teach science outside of school. Those who teach science, who do not perform science activities put forward reasons such as ensuring safety, permit procedure and cost, they think that outdoor learning environments provide students with the opportunity to learn permanently, learn by doing and and through experience, learn in a natural environment; they have difficulty of control and safety problems in these environments, It has been determined that they think that solutions can be found in the design of schoolyards and raising awareness among families.Considering the results of the study, suggestions are presented for what can be done in outdoor learning environments and for future studies.